TEUN A. VAN DIJK’S CRITICAL DISCOURSE ANALYSIS ON THE NEWS TEXT OF THE BINOMO AND INDRA KENZ CASES AT CNBC INDONESIA MEDIA - Ika Sri Ambarwati; Agus Purnomo Ahmad Putikadyanto; Agik Nur Efendi; Aflahah Aflahah (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
The news ‘Indra Kenz Mohon Maaf: Saya Tidak Ada Niat Merugikan dan Menipu’ written by a journalist for CNBC Indonesia, which is felt to have an important role in the reconstruction of news by journalist and the public. The researcher in interested in studying the news ‘Indra Kenz Mohon Maaf: Saya Tidak Ada Niat Merugikan dan Menipu’ using critical discourse analysis approach of Teun A. van Dijk by using element of text analysis and social cognition analysis. The purpose of this study is to find out the text analysis and social cognition in the social cognition in the news ‘Indra Kenz Mohon Maaf: Saya Tidak Ada Niat Merugikan dan Menipu’. The method used in the study is a qualitative research method, with a type of literature research. Data collection techniques used by researchers are interviews and documentation. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. Broadly speaking, this study has two conclusions. First, the text analysis has the results of three structures that form a single unit, namely: macro structure, super structure, and micro structure of the news ‘Indra Kenz Mohon Maaf: Saya Tidak Ada Niat Merugikan dan Menipu’. Second, an analysis of social cognition is carried out by asking questions regarding the content, topic, and background of presenting the news to Muhammad Iqbal as the news writer. The cognition structure does assume that Indra Kenz is a fraud and does not side with him, but journalists still provide space for Indra Kenz to apologize to the public. Journalists use a change of order strategy and place Indra Kenz's apology first in the news